MODEL PENYELESAIAN SENGKETA EKONOMI SYARIAH DI BADAN ARBITRASE SYARIAH NASIONAL - Tehedi Tehedi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The importance of functioning BASYARNAS as a form of non-litigation sharia economic dispute resolution because it has many advantages compared to litigation settlement. Even though there are many advantages, there are still few sharia economic or business actors who use these institutions as an alternative to dispute resolution. This is due to the lack of knowledge and understanding of sharia business actors regarding the forms of settlement at BASYARNAS, so education and literacy are needed for sharia business actors. This study aims to explain the procedure for resolving sharia economic disputes at BASYARNAS. The method used is a qualitative method, a normative juridical approach with a juridical descriptive analysis. The results of this study conclude that the form of sharia economic dispute resolution at BASYARNAS is based on Law no. 49 of 2009 concerning Judicial Power, Law no. 21 of 2008 concerning Islamic Banking, Law no. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, and the 2005 BASYARNAS Procedure Regulations. The settlement procedure begins with a dispute resolution request to BASYARNAS followed by an examination process up to the reading of the decision by a sharia judge or arbiter